Study of the clinical profile and outcome of the neonates born to COVID-19 positive mothers: a tertiary care centre experience from western Uttar Pradesh - Upadhyay, Shobhit; Dayal, Rajeshwar; Nayak, Madhu (International Journal of Contemporary Pediatrics, 2024)
Background: A major concern of SARS-CoV-2 infection in pregnancy is its possible effects on newborns. In the context of mother-to-child transmission, some studies have reported that there were no SARS-CoV-2-positive infants born to a cohort of mothers with COVID-19 while others have reported an incidence of as high as 10%. The study is conducted to describe the clinical profile of neonates born to mothers who tested positive for COVID- 19 infection and to determine the association of neonatal COVID 19 status. Methods: This cross sectional study includes neonates born to COVID 19 positive mothers. Neonates born to mothers who were diagnosed before delivery were tested by RT-PCR within 24 h of birth. Results: Out of 120 babies born to COVID positive mothers, 5 newborns (4.2%) were found to be COVID positive, diagnosed through RT-PCR. Among COVID positive babies four out of five were symptomatic (p<0.001) and required respiratory support in any form (p=0.001). All of the COVID positive neonates were discharged, while there was one mortality noted among covid negative babies (0.9%), however there was no statistically significant association between mortality and COVID infection in the neonates (p=0.498). Conclusions: The proportion of covid positive neonates born to COVID-19-positive women were very low (p=4.2). The study supports milder manifestation in COVID-19 infected neonates and risk of transmission of COVID-19 infection from mother to neonate by rooming in and breastfeeding is low.